2019
DOI: 10.1055/s-0039-1685515
|View full text |Cite
|
Sign up to set email alerts
|

Novel Drivers of the Inflammatory Response in Liver Injury and Fibrosis

Abstract: Hepatocyte demise as well as signals released by stressed hepatocytes have been now recognized as important triggers of liver inflammation. While traditional concepts classically viewed hepatocyte cell death to occur by either a nonlytic, noninflammatory form (apoptosis), or lytic, proinflammatory nonregulated cell death (necrosis), recent studies have provided evidence for additional mechanisms that can contribute to both acute and chronic liver damage. Two novel forms of cell death, pyroptosis and necroptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 75 publications
0
25
0
1
Order By: Relevance
“…Thus, definitive identification of necroptosis requires affirmation by different detection methods and by detection of several kinds of signaling molecular, such as combining the biochemical and morphological tests. Up to now, immunohistochemistry and western blot analyses for phosphor-MLKL are considered acceptable methods to detect necroptosis (41,43).…”
Section: Current Strategies To Detect Necroptosis In the Livermentioning
confidence: 99%
“…Thus, definitive identification of necroptosis requires affirmation by different detection methods and by detection of several kinds of signaling molecular, such as combining the biochemical and morphological tests. Up to now, immunohistochemistry and western blot analyses for phosphor-MLKL are considered acceptable methods to detect necroptosis (41,43).…”
Section: Current Strategies To Detect Necroptosis In the Livermentioning
confidence: 99%
“…Excessive formation of NAPQI consumes intracellular glutathione, binds to mitochondrial proteins, and impairs mitochondrial respiration, which subsequently gives rise to overwhelming mitochondrial oxidative stress that triggers signaling pathways through mitochondrial toxicity, eventually leading to cell death and sterile inflammation (2,3). Importantly, the excessive activation of immune cells, such as Kupffer cells (KCs) causes an inability to shut down the persistent activation of the inflammatory response, which results in tissue damage and disease progression (4)(5)(6)(7). Recent studies have shown that APAP displays dose-dependent toxicity in primary hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Receptor interacting proteins (RIPs) are important cell stress sensors that activate the necroptotic pathway, and the formation of the "necroptosome," a complex containing RIPK1, RIPK3, and mixed lineage kinase domain-like protein (MLKL), leads to membrane lysis and pore formation. The cellular release of DAMPs due to cell membrane disruption is associated with the possible activation of the innate immune system and neighboring cells [21].…”
Section: Necroptosismentioning
confidence: 99%